2015
DOI: 10.1136/thoraxjnl-2015-207770.80
|View full text |Cite
|
Sign up to set email alerts
|

S74 Assessing the diagnostic accuracy of the British Thoracic Society algorithm for investigation of solid pulmonary nodules

Abstract: BackgroundThe British Thoracic Society guidelines (2015) on the investigation and management of pulmonary nodules recommend the use of two risk prediction tools to assess the likelihood of malignancy in solid pulmonary nodules (Brock model following initial CT and the model described by Herder et al. following PET-CT). Management strategies are suggested on the basis of these risk assessments. The aim of this study was to assess the performance of this algorithm in patients with solid pulmonary nodules recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We identified one study 79 that reviewed the outcomes of 211 patients with pulmonary nodules undergoing diagnosis for lung cancer. The study reported that 37 out of 211 patients had nodules of 5-8 mm in diameter, and all were referred to CT surveillance.…”
Section: Small Nodulesmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified one study 79 that reviewed the outcomes of 211 patients with pulmonary nodules undergoing diagnosis for lung cancer. The study reported that 37 out of 211 patients had nodules of 5-8 mm in diameter, and all were referred to CT surveillance.…”
Section: Small Nodulesmentioning
confidence: 99%
“…The Al-Ameri et al 79 study stated that CT surveillance was recommended for 106 patients out of a total sample of 211 (37 with nodule size of < 8 mm, 45 with malignant risk of < 10% following initial CT and 24 with malignant risk of < 10% following PET-CT). Across all of these groups, six had malignant tumours within 2 years of follow-up, suggesting around a 6% risk of malignancy among those referred to CT surveillance.…”
Section: Computerised Tomography Surveillancementioning
confidence: 99%
See 3 more Smart Citations